Korelasi Antara Persepsi Siswa Tentang Peran Guru dan Gaya Belajar Siswa Dengan Prestasi Belajar Pendidikan Aagama Islam - Husnul Mu'amalah (Jurnal Dewantara, 2021)
The aims of this research is to know the level of correlation between student perception about teacher role with learning achievement, learning style with learning achievement, student perception about teacher role and learning style with learning achievement by together. To get the obtained data, writer will process and analyze by using Statistical product and Service Solution (SPSS). From analysis result expressed that, 1) there are significant relation between about teacher role improved, learning achievement also increase, 2) between students learning style variable with student learning achievement. If student learning style improved, learning achievement also increase, 3) between student perception variable about teacher role and student learning achievement by together with student learning achievement.